Correlation of Apo B-48 and Apo B-100 with Oxidized LDL in Men with Central Obesity - Maria Diah Fibriani; Andi Wijaya; Burhanuddin Bahar (The Indonesian Biomedical Journal, 2010)
BACKGROUND: Obesity has a central role in the metabolic syndrome, which raises the risk for atherosclerotic cardiovascular disease (ASVCD). Apo B-48 and Apo B-100 are the necessary structural proteins required for the assembly and secretion of chylomicron and VLDL which have role in atherogenesis. The key initiating process in atherogenesis is the subendothelial retention of apolipoprotein B-containing lipoproteins. Oxidation of LDL is a hallmark of atherosclerosis development. The aim of this study was to asses the association between Apo B-48 and Apo B-100 with Oxidized-LDL as marker of atherosclerosis risk in central obesity. We hope that the result of this study can help to make a new strategy for the prevention and treatment of vascular disease.RESULTS: There were 68 patients aged 39.6±7.3 years, Apo B-48 concentration was 7.47±5.36 μg/mL, Apo B-100 was 117.26±25.74 mg/dL, and ox-LDL was 137.05±18.88 U/L. This study showed a significant correlation between Apo B-100 and ox-LDL (r=0.608, p<0.05) and correlation between Apo B-48 and ox-LDL (r=0.171, p<0.05). The levels of Apo B-100 were significantly different between obese with Mets and obese without Mets individuals (p<0.05).CONCLUSIONS: This study suggested that Apo B-100 concentration increase in obese in Mets as compared with obese without Mets. Apo B-48 and Apo B-100 were correlated with Oxidized LDL, but correlation between Apo B-100 and ox-LDL more significant that Apo B-48and ox-LDL.KEYWORDS: obesity, atherogenesis, Apo B-48, Apo B-100, ox-LDL